Cultural Practices for Vegetable and Small Fruit Crops: Using Kaolin Clay to Reduce Sprinkler Irrigation for Strawberry Transplant Establishment - Bielinski M. Santos; Teresa P. Salame-Donoso; Craig D. Stanley; Alicia J. Whidden; Crystal A. Snodgrass; Mary B. Henry (EDIS, 2011)
Because of the current limitations on water usage for strawberry growers in the Plant City area of Hillsborough County, researchers at the UF/IFAS Gulf Coast Research and Education center have been looking for inexpensive ways to reduce the amount of sprinkler irrigation in strawberry production. This 3-page fact sheet presents research results on the effect of kaolin clay application on sprinkler irrigation volumes applied to newly transplanted strawberries. It was written by Bielinski M. Santos, Teresa P. Salame-Donoso, Craig D. Stanley, Alicia J. Whidden, Crystal A. Snodgrass, and Mary B. Henry, and published by the UF Department of Horticultural Sciences, December 2010.